Cistoadenoma de ovario en embarazo de 36.4 semanas de gestación - Muñoz Loor, Roxana Beatriz (2020)
Serous cystadenomas are diagnosed by histomorphological examination, by pathologists. In general, they are unilocular cysts that contain a clear, straw-colored fluid. Microscopically, the lining of the cyst consists of a simple epithelium with cilia that can be columnar or flat. I present the case of a 22-year-old female patient, primigravida, irregular prenatal control, attended the EMERGENCIES Service at 36.4 weeks of pregnancy, sent by her family doctor for alterations in the fetal heart rate. Physical examination revealed a greater uterus with amenorrhea with a palpable, mobile abdominal mass, with a positive wave sign; Ultrasound revealed a hypoechoic cystic tumor without specifying size, a single live product with delayed intrauterine growth and severe oligohydramnios. Cesarean section is performed obtaining a female product of 2,050 gr. Apgar 9-9, a cystic mass of 30 × 30 × 30 and 12kg of weight was extracted. The histopathological report reported a giant serous cystadenoma of the ovary. The postoperative evolution of the mother and the newborn was satisfactory. Epithelial tumors are the most common ovarian tumors found in pregnancy. Its potential to complicate the development of pregnancy depends fundamentally on its size; in this case, the tumor volume caused intrauterine growth retardation and acute fetal distress, the outcome of which would have been fatal for the product had it not been diagnosed and surgically treated in a timely manner.